Selecting diametric frequency distribution functions for Pinus taeda, Eucalyptus globulus and Eucalyptus dunnii in Uruguay - Hirigoyen, Andrés; Rachid, Cecilia (Bosque (Valdivia), 2017)
The aim of this study was to compare the accuracy of Weibull, reverse Weibull, SB Johnson, Gamma and Beta distributions, fitted with the method of moments and maximum likelihood, for describing diameter distributions in stands of Pinus taeda, Eucalyptus globulus, and Eucalyptus dunnii in Uruguay. Data from 429 permanent plots of P. taeda, 185 plots of E. globulus and 271 plots of E. dunnii were used. To compare the quality of fit for the probability distribution function (pdf), the Kolmogorov-Smirnov and Reynolds error indices were used. The function SB Johnson presented a better fit on the plots of P. taeda, while the inverted Weibull function was more accurate for Eucalyptus species. The method of moments was more accurate than maximum likelihood.